2016
DOI: 10.1002/bjs.10224
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of three targeted approaches to screening for abdominal aortic aneurysm based on cardiovascular risk

Abstract: Different strategies, based on CVD risk, resulted in AAA prevalence rates that were significantly greater than that in CVD-free individuals. This may provide opportunities for a targeted approach to community AAA screening in parts of the world where more sophisticated national screening programmes do not exist.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…Therefore, an effective screening plan could be valuable to prevent extreme AA dilation and rupture and appropriately address high risk patients towards surgery. The importance of an early detection of AA dilatation has been indirectly proven by the observation that AAA and AA rupture can be reasonably excluded in old patients with abdominal pain admitted in emergency department if they had a normal AA size on a previously performed computed tomography or ultrasound exam [31]. A recent study has also shown that a systematic and targeted approach based on CV risk assessment could be very useful to identify undiagnosed cases [32].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, an effective screening plan could be valuable to prevent extreme AA dilation and rupture and appropriately address high risk patients towards surgery. The importance of an early detection of AA dilatation has been indirectly proven by the observation that AAA and AA rupture can be reasonably excluded in old patients with abdominal pain admitted in emergency department if they had a normal AA size on a previously performed computed tomography or ultrasound exam [31]. A recent study has also shown that a systematic and targeted approach based on CV risk assessment could be very useful to identify undiagnosed cases [32].…”
Section: Discussionmentioning
confidence: 99%
“…The association with more CVD risk factors and with CVD history suggests to use the same risk assessment tool used for major CVD, like CVD risk scores. This was the second aim of the RoCAV study, very recently addressed also by Jones et al in selected populations [41]. Our study will address this question in the context of a large sample, randomly selected from the general population.…”
Section: Discussionmentioning
confidence: 92%
“…An AAA screening programme specifically targeted towards higher‐risk groups was not part of this analysis. This is an area of growing interest, for example screening targeted at those with a proven burden of cardiovascular disease or a raised 5‐year cardiovascular risk score, with the goal of a higher AAA detection rate. Separate modelling and assessment would be required for this approach.…”
Section: Discussionmentioning
confidence: 99%
“…Estimating the prevalence of AAA in New Zealand men aged 65 years was difficult given the absence of large population‐based prevalence studies. There have been several smaller AAA prevalence studies in New Zealand between 2005 and 2014. Although they were conducted in different populations and using different imaging modalities, they showed an AAA prevalence in men aged 65 years of between 3 and 8 per cent, particularly in the larger studies that most closely represented a general population.…”
Section: Methodsmentioning
confidence: 99%